2018
DOI: 10.1039/c8tx00061a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ZnO thin film crystallinity on in vitro biocompatibility

Abstract: This study evaluated the cytocompatibility of single- and poly-crystalline ZnO thin films using extract and direct contact methods. Exposure to poly-crystalline ZnO extract resulted in reduced cell viability, on average 82%/70% as measured by MTS/LDH assays, respectively. Direct exposure to both single- and poly-crystalline ZnO thin films resulted in reduced cell viability, which was attributed to anoikis due to inhibition of cell adhesion to the substrate by zinc. Intracellular zinc imaging suggests that sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…A more recent study investigating the in vitro biocompatibility of ZnO nanofilms at the nanoscale found that direct exposure to ZnO nanofilms reduced cell viability of mouse fibroblasts due to inhibition of cell adhesion, regardless of ZnO crystallinity. 154 This study appears to agree with that published by Petrochenko et al 153 and provides further evidence of the adverse effects of ZnO nanocoatings on eukaryotic ( i.e. , host) cells, leading to concerns over the safety and biocompatibility of ZnO nanocoatings in vivo .…”
Section: Types Of Nanocoatingssupporting
confidence: 90%
See 2 more Smart Citations
“…A more recent study investigating the in vitro biocompatibility of ZnO nanofilms at the nanoscale found that direct exposure to ZnO nanofilms reduced cell viability of mouse fibroblasts due to inhibition of cell adhesion, regardless of ZnO crystallinity. 154 This study appears to agree with that published by Petrochenko et al 153 and provides further evidence of the adverse effects of ZnO nanocoatings on eukaryotic ( i.e. , host) cells, leading to concerns over the safety and biocompatibility of ZnO nanocoatings in vivo .…”
Section: Types Of Nanocoatingssupporting
confidence: 90%
“…Research efforts to address the biocompatibility of ZnO nanocoatings have been scant, with most studies looking at ZnO coatings at particle sizes greater than the nanoscale. A more recent study investigating the in vitro biocompatibility of ZnO nanofilms at the nanoscale found that direct exposure to ZnO nanofilms reduced cell viability of mouse fibroblasts due to inhibition of cell adhesion, regardless of ZnO crystallinity . This study appears to agree with that published by Petrochenko et al and provides further evidence of the adverse effects of ZnO nanocoatings on eukaryotic ( i.e.…”
Section: Types Of Nanocoatingssupporting
confidence: 90%
See 1 more Smart Citation
“…However, other nanostructures (e.g. nanowires, nanorods) or thin films have been reported with significantly improved cytocompatibility [78,79], especially when composited with other inorganic and organic agents [80], which is another potential direction for Zn-based nanomaterials.…”
Section: Antibacterial and Biocompatibilitymentioning
confidence: 99%
“…Cytocompatible and biocompatible materials are beneficial to improving the survival rate of loaded cells and alleviating the host response induced by microcarrier implantation [57,58]. Typically, cytocompatibility and biocompatibility can be influenced by both bulk and surface properties [59][60][61][62]. Parameters that influence cytocompatibility and biocompatibility include degradation and toxicity, implant size, charge, hydrophobic-hydrophilic balance, and surface finish (smooth, rough, and surface porosity), among others [61].…”
Section: Properties Of Porous Microcarriersmentioning
confidence: 99%